Interfacial properties and micellization of triblock poly(ethylene glycol)-poly(ε-caprolactone)-polyethyleneimine copolymers - Ji Li; Yitian Du; Haitao Su; Shixuan Cheng; Yanxia Zhou; Yiguang Jin; Xian-Rong Qi (Elsevier, 2020)
This study aimed to explore the link between block copolymers' interfacial properties and nanoscale carrier formation and found out the influence of length ratio on these characters to optimize drug delivery system. A library of diblock copolymers of PEG-PCL and triblock copolymers with additional PEI (PEG-PCL-PEI) were synthesized. Subsequently, a systematic isothermal investigation was performed to explore molecular arrangements of copolymers at air/water interface. Then, structural properties and drug encapsulation in self-assembly were investigated with DLS, SLS and TEM. We found the additional hydrogen bond in the PEG-PCL-PEI contributes to film stability upon the hydrophobic interaction compared with PEG-PCL. PEG-PCL-PEI assemble into smaller micelle-like (such as PEG-PCL4006-PEI) or particle-like structure (such as PEG-PCL8636-PEI) determined by their hydrophilic and hydrophobic block ratio. The distinct structural architectures of copolymer are consistent between interface and self-assembly. Despite the disparity of constituent ratio, we discovered the arrangement of both chains guarantees balanced hydrophilic-hydrophobic ratio in self-assembly to form stable construction. Meanwhile, the structural differences were found to have significant influence on model drugs incorporation including docetaxel and siRNA. Taken together, these findings indicate the correlation between molecular arrangement and self-assembly and inspire us to tune block compositions to achieve desired nanostructure and drug loading.